1990
DOI: 10.1093/nar/18.3.493
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of polyamide-oligonucleotide conjugate molecules

Abstract: We have developed methods for the synthesis of peptide-oligodeoxyribonucleotide conjugate molecules in particular, and polyamide-oligonucleotide conjugates in general. Synthesis is carried out by a solid-phase procedure and involves the assembly of a polyamide on the solid support, conversion of the terminal amino group to a protected primary aliphatic hydroxy group by reaction with alpha, omega-hydroxycarboxylic acid derivatives, and finally oligonucleotide synthesis using phosphoramidite chemistry. The conju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
57
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 20 publications
0
57
0
Order By: Relevance
“…In a different approach, Haralambidis et al [77][78][79][80] reported the derivatization of aminopropylated-CPG with the peptide (Ala-Lys-)sAla (as in 52) toward the preparation of peptideoligodeoxyribonucleotide conjugates. This strategy would also permit the attachment of non-radioactive labels to the lysine residues of the conjugates.…”
mentioning
confidence: 99%
“…In a different approach, Haralambidis et al [77][78][79][80] reported the derivatization of aminopropylated-CPG with the peptide (Ala-Lys-)sAla (as in 52) toward the preparation of peptideoligodeoxyribonucleotide conjugates. This strategy would also permit the attachment of non-radioactive labels to the lysine residues of the conjugates.…”
mentioning
confidence: 99%
“…This was to be expected as it is known that the major pathway for oligonucleotide degradation inside cells is through 3'-exonuclease attack, and we know that the conjugate molecules are resistant to 3'-exonucleases e.g. snake venom phosphodiesterase (Haralambidis et al 1987(Haralambidis et al , 1990a. These molecules also showed a specific antisense inhibition of HIV.…”
Section: Introductionmentioning
confidence: 74%
“…[5][6][7][8] Numerous efforts have been made to increase the cellular uptake of antisense oligonucleotides by covalently attaching various chemical groups. Examples are conjugates with cationic compounds, such as poly-(L)-lysine 9 or polyamides, 10 lipophilic conjugates, such as cholesterol, 11 long chain alcohols, 12 phospholipids, 13 aromatic compounds, 14 as well as polyethylene glycol. 15 Furthermore, the effect of attachment of these compounds at different position of the oligonucleotides including the bases, the backbone and the 3 ' -or 5 ' end was investigated.…”
mentioning
confidence: 99%